Human-Nature Interactions 2022
DOI: 10.1007/978-3-031-01980-7_24
|View full text |Cite
|
Sign up to set email alerts
|

Can Local Knowledge of Small-Scale Fishers Be Used to Monitor and Assess Changes in Marine Ecosystems in a European Context?

Abstract: Significance StatementIn the last decades, many coastal areas have observed dramatic changes in marine ecosystems, due to anthropogenic and environmental alterations. The general absence of long-term data sets in the marine environment and, more specifically, on benthic and demersal communities represents a severe issue for management and conservation. We propose to incorporate the small-scale fishers’ knowledge and science for better policy recommendations, both in terms of fisheries optimization and resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This could be attributed to the presence of other habitat-forming species that could be playing the role of the Laminaria spp. in this region (Piñeiro-Corbeira et al, 2022), such as the seasonal species S. polyschides and/or Cystoseira sensu lato. According to recent studies, these species have increased their frequency of occurrence in this region in parallel to the loss of Laminaria spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be attributed to the presence of other habitat-forming species that could be playing the role of the Laminaria spp. in this region (Piñeiro-Corbeira et al, 2022), such as the seasonal species S. polyschides and/or Cystoseira sensu lato. According to recent studies, these species have increased their frequency of occurrence in this region in parallel to the loss of Laminaria spp.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of kelp forests for coastal ecosystems and the communities that live from their resources, only a few studies have been carried out on the ecology of kelp forests in NW Spain as well as on their social, economic, and cultural importance (Barrientos et al, 2022a;Barrientos et al, 2022b;Piñeiro-Corbeira, et al, 2022). However, information on SSFs and their catches is not easily available , which makes collaborative activities essential for fisheries research and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from the University of La Laguna showed the area has recovered (Lazzari 2015;Mendoza et al 2020), and commercial fishers agree. Between 2013 and 2014, fishers came back to their main traditional small-scale fisheries and fishing grounds (Piñeiro-Corbeira et al 2022). Also, marine tourism activity in the area entirely recovered (Fig.…”
Section: The Marine Reserve and The Marine Tourism Developmentmentioning
confidence: 99%